2014 IEEE International Electron Devices Meeting 2014
DOI: 10.1109/iedm.2014.7047121
|View full text |Cite
|
Sign up to set email alerts
|

New insights on bottom layer thermal stability and laser annealing promises for high performance 3D VLSI

Abstract: For the first time the maximum thermal budget of in-situ doped source/drain State Of The Art (SOTA) FDSOI bottom MOSFET transistors is quantified to ensure transistors stability in Sequential 3D (CoolCube TM ) integration. We highlight no degradation of Ion/Ioff trade-off up to 550°C. Thanks to both metal gate work-function stability especially on short devices and silicide stability improvement, the top MOSFET temperature could be relaxed up to 500°C. Laser anneal is then considered as a promising candidate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…To ensure a local thermal budget of the bottom MOSFET in this 400-500°C range alternative thermal processing like laser annealing [11,12] could be envisaged to perform dopant activation. Indeed, Laser anneal thanks to its low in-depth thermal diffusion is a promising opportunity for top transistor dopant activation: it is expected to provide high activation together with surface confined heating [13]. For example an Excimer (wavelength: 308 nm, pulse duration: $200 ns) as presented in [13] could be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure a local thermal budget of the bottom MOSFET in this 400-500°C range alternative thermal processing like laser annealing [11,12] could be envisaged to perform dopant activation. Indeed, Laser anneal thanks to its low in-depth thermal diffusion is a promising opportunity for top transistor dopant activation: it is expected to provide high activation together with surface confined heating [13]. For example an Excimer (wavelength: 308 nm, pulse duration: $200 ns) as presented in [13] could be used.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Laser anneal thanks to its low in-depth thermal diffusion is a promising opportunity for top transistor dopant activation: it is expected to provide high activation together with surface confined heating [13]. For example an Excimer (wavelength: 308 nm, pulse duration: $200 ns) as presented in [13] could be used. To overcome dopant deactivation one solution consists in using a single type of dopant As or P with a reduced implantation dose as proposed in [14].…”
Section: Discussionmentioning
confidence: 99%
“…In Section 2, we described that the main challenge for sequential F2B is to achieve high-performance transistors across all tiers within a low-thermal fabrication process. However, we have to point out that despite technical challenges, promising solutions are under development as was recently presented [3].…”
Section: Block-level 3dv Implementationmentioning
confidence: 97%
“…This implies that the performance of the top tier may not be the same as that of the bottom tier. Recently, [3] quantifies the maximum thermal budget of in-situ doped source / drain fully depleted silicon-on-insulator (FDSOI) MOSFET transistors to ensure transistor stability in sequential F2B integration. Due to silicide stabil- ity improvement, the top MOSFET temperature could be relaxed up to 500 • .…”
Section: DV Fabrication Process and Is-suesmentioning
confidence: 99%
“…Amorphous or polycrystalline TFTs are easy to fabricate and can be integrated onto CMOS wafers at temperature below 400 C. There are also research efforts to stack single-crystal silicon film for transistor fabrication on top of silicon CMOS circuits. It has been shown that the top silicon transistor process temperature can be relaxed down to 500 C without degrading the bottom silicon transistors' performance and promising results have been obtained with laser annealing for junction activation [23]. However, the relatively small throughput of laser annealing would be a concern.…”
Section: A Cmos-backend-compatible Transistorsmentioning
confidence: 98%